Different Oxidative Stress and Inflammation Patterns of Diseased Left Anterior Descending Coronary Artery versus Internal Thoracic Artery - Andrea Salica; Vittoria Cammisotto; Raffaele Scaffa; Giulio Folino; Ruggero De Paulis; Roberto Carnevale; Umberto Benedetto; Wael Saade; Antonino Marullo; Sebastiano Sciarretta; Gianmarco Sarto; Silvia Palmerio; et al. (MDPI AG, 2024)
Background. Oxidative stress and inflammation are typically implied in atherosclerosis pathogenesis and progression, especially in coronary artery disease (CAD). Our objective was to investigate the oxidative stress and inflammation burden directly associated with atherosclerotic plaque in patients with stable coronary disease undergoing coronary artery bypass graft (CABG) surgery. Specifically, markers of oxidative stress and inflammation were compared in blood samples obtained from the atherosclerotic left anterior descending artery (LAD) and blood samples obtained from the healthy left internal thoracic artery (LITA), used as a bypass graft, within the same patient. Methods. Twenty patients scheduled for off-pump CABG were enrolled. Blood samples were collected from the LITA below anastomosis and the LAD below the stenosis. Samples were analysed for oxidative stress (sNOXdp, H2O2, NO) and inflammation markers (TNFα, IL-6, IL-1β, IL-10). Results. The analysis showed a significant increase in oxidative stress burden in the LAD as compared to LITA, as indicated by higher sNOX2-dp and H2O2 levels and lower NO levels (p < 0.01). Also, pro-inflammatory cytokines were increased in the LAD as compared to the LITA, as indicated by higher TNFα and IL-6 amounts (p < 0.01). On the other hand, no significant differences could be seen regarding IL-1β and IL-10 levels between the two groups. Conclusions. The oxidative stress and inflammatory burden are specifically enhanced in the LAD artery of stable coronary patients compared to systemic blood from the LITA of stable coronary patients.